Avaliação dos mecanismos de toxicidade do disseleneto de difenila (PhSe)2 e cloreto de fenilselênio zinco (PhSeZnCl) em Saccharomyces cerevisiae - Galant, Leticia Selinger (2015)
Selenium (Se) is a microelement present in different animal tissues in the form of selenoproteins, for example, the glutathione peroxidase (GPx). Organic selenium compounds, such as diphenyl diselenide (PhSe)2 and fenilselenium zinc chloride (PhSeZnCl) have presented GPx mimetic activity in the degradation of hydrogen peroxide. However the protective effects are dependent on the dose evaluated. High concentrations of these compounds can provide oxidation in protein thiol groups and leading to increase of reactive oxygen species (ROS) production. However, studies of cellular mechanisms in the toxicity of these compounds were not completely understood. Thus, this study aimed to investigate the mechanisms of toxicity (PhSe)2 and PhSeZnCl, through the ROS production and morphological alterations in Saccharomyces cerevisiae. The samples were incubated for 1, 2, 3, 4, 6 and 16 hours with (PhSe)2 in concentrations of 2, 4, 6 and 10 μM. PhSeZnCl was only incubated at 16 hours in concentrations of 4, 8, 12 and 20 μM. Cell growth was analyzed by spectrophotometry. Through flow cytometry was analyzed ROS production by fluorescence of dichlorofluorescein diacetate (DCFH-DA), cell membrane permeability by propidium iodide (PI), cells size and granularity. Total thiol groups were analyzed by the colorimetric reaction with DTNB. (PhSe)2 was able to inhibit cell growth after 2 h incubation in 10 μM followed by an increase in cell membrane permeability. The increase in cell size and granularity was observed after 3 h of incubation. However the ROS production was observed only at 16 h of incubation in 10 μM. The total of thiol groups increased in 6 μM of (PhSe)2 after 16 h of incubation. When yeast cells were treated with PhSeZnCl, this compound showed toxicity only at concentrations of 20 μM in all parameters tested. We concluded that the toxicity of (PhSe)2 is not directly related to production of ROS. PhSeZnCl apparently is less toxic than the (PhSe)2.